Targeting the Aryl Hydrocarbon Receptor with Microbial Metabolite Mimics Alleviates Experimental Colitis in Mice - Grycová, Aneta; Joo, Hansol; Maier, Vítězslav; Illés, Peter; Vyhlídalová, Barbora; Poulíková, Karolína; Sládeková, Lucia; Nádvorník, Petr; Vrzal, Radim; Zemánková, Lenka; Pečinková, Petra; Poruba, Martin; et al. (Journal of medicinal chemistry, 2022)
Targeting the aryl hydrocarbon receptor (AhR) is an emerging therapeutic strategy for multiple diseases (e.g., inflammatory bowel disease). Thermosporothrix hazakensis microbial metabolite 2-(1'H-indole-3'-carbonyl)-thiazole-4-carboxylic acid methyl ester (ITE) is a putative AhR endogenous ligand. To improve the chemical stability, we synthesized a series of ITE chemical mimics. Using a series of in vitro assays, we identified 2-(1H-indole-3-carbonyl)-N-methyl thiazole-4-carboxamide (ITE-CONHCH3) as a highly potent (EC50 = 1.6 nM) AhR agonist with high affinity (Ki = 88 nM). ITE-CONHCH3 triggered AhR nuclear translocation and dimerization of AhR-ARNT, enhanced AhR binding in the CYP1A1 promoter, and induced AhR-regulated genes in an AhR-dependent manner. The metabolic stability of ITE-CONHCH3 in a cell culture was 10 times higher than that of ITE. Finally, we observed protective effects of ITE-CONHCH3 in mice with DSS-induced colitis. Overall, we demonstrate and validate a concept of microbial metabolite mimicry in the therapeutic targeting of AhR.
Keywords: Cytochrome P-450 CYP1A1; Thiazoles; Receptors, Aryl Hydrocarbon; myši; Colitis; receptory aromatických uhlovodíků; thiazoly; kolitida; Animals; Mice; cytochrom P-450 CYP1A1; Indoles; zvířata; indoly